Effects of tea polyphenol palmitate on the crystallization of rice bran oil. (March 2021) - Wang, Yong; Zhou, Shuai; Jiang, Yuanrong; Li, Cheng; Zhu, Zhennan; Wang, Xin; Liu, Lvrui; Sun, Yue; Zheng, Cong; Guan, Xiao
Abstract: The quality of rice bran oil (RBO) is significantly affected by its poor cold performance. The effects of the addition of tea polyphenol palmitate (TE) on the improvement of the cold performance of RBO were investigated. The results indicated that RBO remained clear at 0 °C for 5.5 h when the TE concentration was 0.08 wt%, and TE could recrystallize in RBO before RBO crystallization and further promote the nucleation of RBO crystallization. The mechanism of which TE promoted the cold performance of RBO was proposed. The partially recrystallized TE crystal could act as a nucleating agent to promote nucleation and refine crystal size. However, hydrogen bonds between the hydroxyl groups of the residual TE and the carbonyl groups of triglyceride formed which limited the movement of the RBO molecular chain and hindered the growth of the RBO crystal. Rheological and Fourier transform infrared spectroscopy experimental evidences supported this mechanism. Highlights: TE can improve the cold performance of rice bran oil. TE can precipitate before rice bran oil crystallization. TE promoted the nucleation of rice bran oil crystallization. Hydrogen bonds can form between –OH of TE and CO of triglyceride.